If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4x-8)=(3x-1)
We move all terms to the left:
(4x-8)-((3x-1))=0
We get rid of parentheses
4x-((3x-1))-8=0
We calculate terms in parentheses: -((3x-1)), so:We get rid of parentheses
(3x-1)
We get rid of parentheses
3x-1
Back to the equation:
-(3x-1)
4x-3x+1-8=0
We add all the numbers together, and all the variables
x-7=0
We move all terms containing x to the left, all other terms to the right
x=7
| -18+5x=-5(-x+4)-5 | | 10+8m=46 | | 12x+5x-3=117 | | x+65=9x+25 | | 3(m-5)=17 | | x+4-6=-10 | | -4(6x+3)=2(-7x+6)-10x | | −8+4y=2(2y−4) | | -10=-2k+6(2k-10)-30 | | 3x+13x+350=1630 | | 3a+1=100 | | 4(22-8)=16y | | 3y-4y=y | | 6^x+10=39 | | 36=4(3-6x) | | -10=-2k+6{2k-10}-30 | | 6x+2x=2x-12 | | 4x-(x+15)= | | 7k+3=4k+54 | | 4(2p+3)=20 | | 0.80x-40=23 | | 0.6x^{2}+x+970=0 | | 8.4x-3.4=55.4 | | 11a+8=-2(1-4a)+9 | | 8x2+4-16=-x | | 3.8a=5 | | (x+5)/3=-10 | | 500=t | | 4-(3x-2)+6x+9= | | 11a+8=-2(1-4a)+a | | -5g+3=3+10g | | 6x+2+128=50 |